Limited Carbonate Dissolution by Boring Microflora at Two Volcanically Acidified Temperate Sites: Ischia (Italy, Mediterranean Sea) and Faial (Azores, NE Atlantic Ocean). Issue 1 (17th January 2018) - Tribollet, A.; Grange, J. S.; Parra, H.; Rodolfo‐Metalpa, R.; Carreiro‐Silva, M.
Abstract: In situ effects of ocean acidification on carbonate dissolution by microboring flora, also called biogenic dissolution, have only been studied once in tropical environments. Naturally acidified seawaters due to CO2 vents offer a perfect setting to study these effects in temperate systems. Three sites were selected at Ischia (Italy, Mediterranean Sea) with one experiencing ambient pH and the two others a mean pHT of 7.2 and 7.5. At Faial (Azores, NE Atlantic), one site with ambient pH and one acidified site with a mean pHT of 7.4 were selected. Experiments were carried out during 1.5 months and 6 months in Azores and Ischia, respectively, to determine the effects of OA on microboring communities in various carbonate substrates. Low pH influenced negatively boring microflora development by limiting their depth of penetration and abundance in substrates. Biogenic dissolution was thus reduced by a factor 3 to 7 depending on sites and substrate types. At sites with ambient pH in Faial, biogenic dissolution contributed up to 23% to the total weight loss, while it contributed less than 1% to the total weight loss of substrates at the acidified sites. Most of the dissolution at these sites was due to chemical dissolution (often Ω ≤ 1). Such conditions maintained microboring communities at a pioneer stage with a limited depth of penetration in substrates. Our results, together with previous findings that showed an increase of biogenic dissolution at pH > 7.7, suggest that there is a pH tipping point below which microborer development and thus carbonate biogenic dissolution is strongly limited. Key Points: Natural microboring communities actively dissolved aragonite and calcite substrates in temperate systems at Ischia (Italy) and Faial (Azores) even at pH 7.2 Chemical dissolution of carbonates at the CO2 vent sites (due to Ω ≤ 1) maintained microboring communities at a pioneer stage and thus limited their erosive activity Our results suggest that there is a pH threshold between 7.4 and 7.7 below which biogenic dissolution of carbonates by microborers is strongly limited